Analisis Dampak Lembaga Keuangan Mikro Syariah terhadap Pencapaian SDGs: Studi Kasus BMT IMADA Kuningan - Ade Kurniawan; Arip Rahman (Department Islamic Economics, 2025)
Through analysis of BMT Imada Kuningan as a case study, this research evaluates the impact of Sharia microfinance institutions (LKMS) on achieving SDGs. The main objective of this research is to understand the role, evaluation and impact of Sharia Microfinance Institutions from BMT Imada in achieving the SDGs and provide recommendations to improve the operational effectiveness and efficiency of BMT Imada. Research is still limited. The scope of SDGs points referred to in this scope only includes SDGs (1), SDGs (8) and SDGs (10). This research uses the Analytic Network Process (ANP) method to process qualitative and quantitative data. The findings of this research indicate that the assessment of sharia microfinance institutions has not made a significant contribution to achieving SDGs in the surrounding environment. The main problem faced by LKMS BMT Imada is the micro scale, which is indicated by the low capital owned by LKMS, with a priority value of 0.25123. Meanwhile, problems related to sharia principles, where members do not understand the concept of sharia, are busy with the last priority with a value of 0.15202. The solution to overcome this is to focus on internal strengthening of BMT through increasing sharia financial literacy among members and optimizing capital management. Digitalization is also considered an important step to increase operational efficiency, expand fund distribution, and strengthen communication and outreach to members and the public.